Contamination source, health and ecological risk assessment of hazardous elements in the sediment of the Shahid Rajaee reservoir - Kachoueiyan, Fatemeh; Alipour Atmianlu, Pourya; Rajabi, Armin; Ustaoğlu, Fikret; Karbassi, Abdolreza (Frontiers in Environmental Science, 2024)
Sediment pollution from potentially hazardous elements (PHE) generated by human activity has grown into a worldwide problem. In this regard, for the first time, surface sediment samples were obtained from six points along the Shahid Rajaee Reservoir for this investigation. Elements concentrations (Cu, Cr, Co, Mn, Fe, Pb, Ni, and Zn) were assessed using ICP-MS. Based on the individual indices (geoaccumulation index, contamination factor), all elements at all sample sites were found to be low in contamination, except Pb and Zn (at sites 1 and 2). The combined effect of PHEs in the sediment samples did not show a considerable concern, according to the synergistic indices. The health risk assessment revealed that recreational receptors were unlikely to face non-carcinogenic or carcinogenic hazards as a consequence of exposure to PHEs in sediments with unintentional ingesting and contact with the skin. The Tessier technique demonstrated that all PHEs were mostly connected with the oxidizable fraction. According to statistical study, while Cu, Co, Cr, Ni, Fe, and Mn were obtained from lithogenic sources, Pb and Zn came from natural as well as human-made sources.